Hepatoprotective Activity of the Ethanolic Extract of Polygonum multiflorum Thunb. against Oxidative Stress-Induced Liver Injury. (17th October 2018) - Lin, En-Yuan; Chagnaadorj, Amarzaya; Huang, Shyh-Jer; Wang, Ching-Chiung; Chiang, Yung-Hsiao; Cheng, Chao-Wen
Abstract : Oxidative stress is an important pathological mechanism in various liver diseases. Polygonum multiflorum Thunb. (PM) can be used for the treatment of diseases associated with aging, hyperlipidemia, and oxidative stress in traditional Chinese medicine. In this study, we examined the hepatoprotective effects of the ethanolic extract of PM (PME) in in vitro and in vivo models. The PME induced expression of antioxidant-response-element- (ARE-) related genes in HepG2 cells showed a dose-dependent manner. Pretreatment of HepG2 cell with PME suppressed H2 O2 - and acetaminophen- (APAP-) induced cellular reactive oxygen species (ROS) generation and cytotoxicity. In APAP-induced mouse liver injury, pretreatment with PME also showed ability to increase the survival rate and reduce the severity of liver injury. Treatment with PME attenuated bile duct ligation-induced extrahepatic cholestatic liver injury and further increased multidrug resistance protein 4 (MRP4) and reduced organic anion-transporting polypeptide (OATP) expression. Furthermore, increased nuclear translocation of the nuclear factor erythroid 2-related factor 2 (Nrf2) was observed after treatment with PME in both in vivo models. In conclusion, the current study showed the hepatoprotective activity of PME by regulating the redox state in liver injury through Nrf2 activation and controlling hepatic bile acid homeostasis in obstructive cholestasis, through bile acid transporter expression modulation.